THE INFLUENCE OF WORKLOAD, CAREER DEVELOPMENT, AND COMPENSATION ON TURNOVER INTENTION AT PT PRIMA UFUK SEMESTA - Kurniawan, Prasetyo; Solihin, Dede (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
This study aims to examine and analyze the effect of workload, career development, and compensation on turnover intention at PT Prima Ufuk Semesta. The population in this study were all employees of PT Prima Ufuk Semesta. The sampling technique was saturated sampling so that a total sample of 60 respondents was obtained. The research was conducted by distributing questionnaires. The analytical method uses the Structural Equation Model (SEM) approach with the Smart PLS 3.0 analysis tool. The results of the study show that workload has a positive and significant effect on turnover intention. This can be interpreted that the higher the workload received by employees will be able to increase employee turnover intention. Career development has a negative and significant effect on turnover intention. This can be interpreted that the higher the career development received by employees will be able to reduce employee turnover intention. Compensation has a negative and significant effect on turnover intention. This can be interpreted that the higher the compensation received by employees will be able to reduce employee turnover intention.